Alkaloids from Alstonia Macrophylla / Lim Siew Huah - Lim, Siew Huah (2013)

(untitled)
The Malaysian plant, Alstonia macrophylla Wall, was investigated for its alkaloidal content and the results are summarized in the Table below. A total of 90 alkaloids were isolated and characterized from the leaf and stem-bark of A. macrophylla. Of these, 30 are new alkaloids. The leaf extract of A. macrophylla yielded a total of 13 new alkaloids, including a macroline indole 1, a macroline oxindole 16, eight akuammiline alkaloids (compounds 24, 25, 26, 27, 28, 29, 30, and 31), a sarpagine alkaloid 32, and two ajmaline alkaloids (compounds 33 and 34). The stem-bark extract of A. macrophylla gave a total of 19 new alkaloids. These include, in addition to the akuammiline and sarpagine alkaloids found in the leaf extract (24 and 32, respectively), compound 2, 3, 4, 17, the linearly fused bisindole alkaloids, lumutinines A‒E (7175), the macroline-macroline bisindoles, lumusidines AD (7780) and perhentidines A‒B (81and 82), and the macrolinepleiocarpamine bisindole alkaloids, villalstonidines B (86) and F (87). Perhentidines A‒B (81 and 82), perhentinine (83), villalstonine (88) and macrocarpamine (90), showed pronounced cytotoxicity toward KB cells (IC50 2.644.06 g/mL), while lumutinines A‒E (71‒75), macralstonidine (76), lumusidines A-C (77‒79), anhydromacralstonine (85), and villalstonidine B (86) showed moderate cytotoxicity toward KB cells (IC50 4.3018.14 g/mL). Compounds 24, 25, 26, 29, 31, 32, lumusidine D (80), and macralstonine (84) showed strong activity in circumventing MDR in vincristine-resistant KB cells (IC50 0.055.03 g/mL).